Chiral Amplification by L‐Cysteine‐Capped Gold Nanoparticles in Lyotropic Chromonic Liquid Crystals. Issue 12 (24th October 2017) - Bergquist, Leah; Hegmann, Torsten
Abstract: Transfer of chirality from an adsorbed molecule to a metal nanoparticle surface, and from the resulting chiral nanoparticle to its surroundings, depends on numerous factors – structure of the adsorbed molecule, its size and shape, and its interactions with its specific environment – but is often difficult to understand and even more difficult to measure, visualize, and quantify. This severely limits the potential of chiral nanoparticles in a range of emerging applications as optical metamaterials, enantioselective catalysts, or chiral discriminators for biomacromolecules. We examine if chirality at the nanoscale (i. e. in gold nanoparticles capped with chiral ligand molecules) is uniquely able to generate more intense responses than their organic chiral counterparts in soft condensed matter utilizing lyotropic chromonic liquid crystals (LCLCs) forming the nematic phase. As a powerful manifestation of nanoscale chiral amplification, we show that L ‐cysteine capped gold nanoparticles induce a tighter chiral twist within, and similar among, stacks of nematic LCLCs with several orders of magnitude fewer chiral L ‐cysteine ligands in comparison to the free molecular L ‐amino acid. Abstract : An asthma drug reporting chiral amplification : The lyotropic chromonic liquid crystal nematic phase formed by disodium cromoglycate (DSCG) in water is used to elucidate the substantial chiral amplification by chiral L ‐cysteine‐capped gold nanoparticles vs. the neat, non‐bound amino acid.